DEVELOPMENT OF THE OPPORTUNITY MODULE TO IMPROVE HIGH SCHOOL LEVEL UNDERSTANDING ABILITY OF MATHEMATICAL CONCEPTS - Defi Yanti Hulu; Leni Marlina Laia; Defi Susanti Duha (Universitas Nias Raya, 2023)
This research aims to improve the module which refer to the developing of understanding the mathematics concept. The teaching material of this lesson sets is opportunity material. The procedure of module development that used in this research is 4D development module (Define, Design, Develop, Disseminste). The instrument that used in this research to measure the validity of module, responsive students’ of question are to measure the practicality of module, and the sheet of pretest-posttest validity to measure the effectivity of mathematics module. Based on the validity test, the result of this research should that opportunity module was valid with the percentage of validity level was 96,83%. The result of practicality for the tes in limited group was 3.47 with the percentage 83,4% was categorized very practical. The result of the effectivevess test in limited group with the acquisition of values was 80% in effective categori, and the result of of test in controlled class with the axquisition values was 85,3% in effective category. The students’ ability in understanding the mathematics concept increased to 0,79 in bigh category. This result showed that the develompment of the module was valid, practical and effective and able to improve the stundents’ ability in understanding the mathematics concept. This module suggested to be used to improve the students’ ablitiy in understanding mathematics concept in opportunity material